The contribution of the Poltava ornithologist M.I. Gavrilenko studying birds of Ukraine and the Soviet Union - M. M. Rohozha (History of science and technology, 2015)
The paper exposes the contribution of one of the most hardworking faunists M.I.Havrylenko, who researched Poltava area bird fauna, as well as applications of results he obtained in multivolume editions, such as “Fauna of Ukraine”, “Birds of the Soviet Union” and bibliography index “Birds of the USSR”. Also, the paper enlightens little-known pages of his life and scientific activity; his biography is enriched by them.